Overview of Efforts to Increase Women Enrollment in the Veterans Affairs Million Veteran Program - Collaboration group; Collaboration group (Mary Ann Liebert, 2023)
Background: Ensuring enhanced delivery of care to women Veterans is a top Veterans Affairs (VA) priority; however, women are historically underrepresented in research that informs evidence-based health care. A primary barrier to women's participation is the inability to engage with research in person due to a number of documented challenges. The VA Million Veteran Program (MVP) is committed to increasing access for women Veterans to participate in research, thereby better understanding conditions specific to this population and how disease manifests differently in women compared to men. The goal of this work is to describe the results of the MVP Women's Campaign, an effort designed to increase outreach to and awareness of remote enrollment options for women Veterans. Materials and Methods: The MVP Women's Campaign launched two phases between March 2021 and April 2022: the Multimedia Phase leveraged a variety of strategic multichannel communication tactics and the Email Phase focused on direct email communication to women Veterans. The effect of the Multimedia Phase was determined using t-tests and chi-square tests, as well as logistic regression models to compare demographic subgroups. The Email Phase was evaluated using comparisons of the enrollment rate across demographic groups through a multivariate adjusted logistic regression model. Results: Overall, 4694 women Veterans enrolled during the MVP Women's Campaign (54% during the Multimedia Phase and 46% during the Email Phase). For the Multimedia Phase, the percentage of older women online enrollees increased, along with women from the southwest and western regions of the United States. Differences for women Veteran online enrollment across different ethnicity and race groups were not observed. During the Email Phase, the enrollment rate increased with age. Compared to White women Veterans, Blacks, Asians, and Native Americans were significantly less likely to enroll while Veterans with multiple races were more likely to enroll. Conclusion: The MVP Women's Campaign is the first large-scale outreach effort focusing on recruitment of women Veterans into MVP. The combination of print and digital outreach tactics and direct email recruitment resulted in over a fivefold increase in women Veteran enrollees during a 7-month period. Attention to messaging and communication channels, combined with a better understanding of effective recruitment methods for certain Veteran populations, allows MVP the opportunity to advance health and health care not only for women Veterans, but beyond. Lessons learned will be applied to increase other populations in MVP such as Blacks, Hispanics, Asians, Native Americans, younger Veterans, and Veterans with certain health conditions.